2019 Computing in Cardiology Conference (CinC) 2019
DOI: 10.22489/cinc.2019.052
|View full text |Cite
|
Sign up to set email alerts
|

Sleep RR-Interval U-patterns and Their Correlation to Movement Events

Abstract: The aim of this work is to investigate the relation between a phenomenon called "U-patterns" and their possible correlation to movement events in the context of sleep deprivation. U-patterns take place in the RR-interval time series during sleep. As their name suggests, these patterns present a U-shaped decrease-increase in RR-intervals, with a duration lasting from 20 to 40 seconds together with a minimum decrease of 15% in the local RR mean value.Over a span of 17 days, 15 healthy subjects (7males, 22.1 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is not completely clear which physiological mechanisms trigger U-shaped patterns in humans. Yazdani et al using polysomnography recordings reported moderate correlation with movements during sleep [2]. In the literature we found many examples of acceleration-deceleration periods of RR time intervals during sleep associated with the sighs, leg movements, sleep apnea (i.e.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is not completely clear which physiological mechanisms trigger U-shaped patterns in humans. Yazdani et al using polysomnography recordings reported moderate correlation with movements during sleep [2]. In the literature we found many examples of acceleration-deceleration periods of RR time intervals during sleep associated with the sighs, leg movements, sleep apnea (i.e.…”
Section: Introductionmentioning
confidence: 73%
“…They are, in a domain of RR time intervals, the most laminar structures in nightrime recordings. They are defined as accelerationdeceleration periods in RR interval series, with duration between 20-40 s, and amplitude at smaller at least than 85% of the mean RR interval [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In our article, we defined a U-shaped pattern as an acceleration-deceleration event, where the acceleration takes a longer time than the deceleration following it with a duration within 20-40 s and an amplitude smaller than 85% of the mean RR interval (similar criteria were used by Yazdani et al (2018Yazdani et al ( , 2019). In the Discussion section of the article, we showed that heart rate responses observed during sighs and periodic leg movements are shorter and weaker (in amplitude) than U-shaped patterns (see also Perez-Padilla et al (1983) and Winkelman (1999)).…”
mentioning
confidence: 99%